The Safety of 4-valent Meningococcal Conjugate Vaccine in Two Years Old Children: Prospective Cohort Study in Sakhalin Region - Oxana V. Solonina; Tatiana M. Sy; О. В. Солонина; Т. М. Сы (Current Pediatrics, 2019)
Background. Acceptability of routine immunization with vaccine to meningococcus serogroups A, C, W, Y in Russian children have not been studied earlier. Objective. The aim of the study was to understand the safety of polyvalent meningococcal conjugate vaccine administration in two years old children in actual clinical practice. Methods. The vaccination of two years old children against meningococcal disease has been performing in Sakhalin region since April 2018. All children who received single 4-valent meningococcal conjugate vaccine to A, C, W, Y serogroups in the period from April to November 2018 were included into the research. The vaccine safety in general group was estimated by local pediatricians visiting due to general and local adverse effects on vaccine injection in one month period. Safety study for children vaccinated in the period from September to October 2018 was carried out by questioning parents. Results. 1250 children were vaccinated during this research. Local paediatricians has recorded 11 (0.9%) appointments due to adverse effects within 1 month after vaccination. All of them were mild: infiltrates in the vaccine injection site (4 cases), high temperature up to 38°C (7 cases). Survey of 100 parents has shown that at least one adverse effect in 4 weeks period was noted only in 23 children: local reactions (induration, redness at the injection site) in 14 cases, general reactions (temperature increase up to 38.7°C) in 9 cases. No adverse effects needed medical intervention. Conclusion. Adverse effects were recorded in less than 1% of all cases according to local paediatricians appointments and in every 4th case according to parents questioning among all two years old children who undergone immunization with 4-valent meningococcal conjugate vaccine to A, C, W, Y serogroups. Обоснование. Переносимость российскими детьми рутинной иммунизации вакциной к менингококкам серогрупп A, C, W, Y ранее не изучалась. Цель исследования — изучить безопасность применения поливалентной конъюгированной ...